Between the will of the contracting parties and the needs of today - Mowbray, Alastair (Cambridge University Press, 2014)
This chapter will ascertain the intentions of the drafters of the European Convention on Human Rights (hereafter the ECHR or Convention) and then examine a number of factors that have resulted in the judicial expansion of the rights and freedoms enshrined in its text. The genesis of the Convention predates the creation of the inter-state organisation the Council of Europe. In 1948 a collection of non-governmental groups, favouring unity in western Europe, held the ‘Congress of Europe’. The Congress ended with a five-point declaration that included: ‘…(2)[w]e desire a Charter of Human Rights guaranteeing liberty of thought, assembly and expression as well as the right to form a political opposition; (3) [w]e desire a Court of Justice with adequate sanctions for the implementation of the Charter…’. During the next year a triumvirate of rapporteurs drafted a European Convention on Human Rights and a Statute of the European Court of Human Rights (hereafter the Court) for the ‘European Movement’. Following the establishment of the Council of Europe these two drafts were submitted to the highest political body of the Council, the Committee of Ministers. In turn the Committee of Ministers authorised the discussion of the development of such a Convention by the Council's Consultative Assembly. The ensuing debates revealed the rapporteurs, taking account of the political need to secure state agreement to the substance of the Convention, adopting circumscribed views towards the scope of the Convention's guarantees. For example, Teitgen considered that the Convention should embody a ‘collective guarantee’ of a limited set of rights: ‘security of person; freedom from arbitrary arrest; freedom from slavery and servitude; freedom of speech and expression; freedom of religious belief, practice and teaching; freedom of association and assembly; the natural rights derived from marriage and paternity and those pertaining to the family, the sanctity of the home, equality before law, protection from discrimination on account of religion, race, national origin, political or philosophical opinion; freedom from arbitrary deprivation of property’.